The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s10488-016-0745-2
|View full text |Cite
|
Sign up to set email alerts
|

Common Mental Disorder Diagnosis and Need for Treatment are Not the Same: Findings from the NEMESIS Study

Abstract: The study aimed to determine whether some depressive, anxiety, and substance-use (DAS) disorders are mild, transient cases that remit without treatment. The first two waves of the first Netherlands Mental Health Survey and Incidence Study were used (age 18-64 years at baseline; wave two N = 5618). Mental disorders were assessed using CIDI 1.1. Past-year and past-month measures of DAS disorders, health service use, and quality of life were assessed at both waves. Individuals with a past-year DAS disorder who re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 32 publications
3
22
0
1
Order By: Relevance
“…Heterogeneity of study designs and outcome definitions were large and hampered statistical analysis. Recent naturalistic long-term outcome studies comparing ADM-treated and untreated individuals with diagnosed depression consistently corroborate the findings of Hughes and Cohen's review (Bockting, Hollon, Jarrett, Kuyken, & Dobson, 2015;Hengartner, Angst, & Roessler, 2018;Nuijen, ten Have, Tuithof, van Dorsselaer, & van Bon-Martens, 2014;Verduijn et al, 2017;Vittengl, 2017;Wang et al, 2017). Statistical adjustment for confounders (e.g.…”
Section: Psychological Medicinesupporting
confidence: 66%
See 1 more Smart Citation
“…Heterogeneity of study designs and outcome definitions were large and hampered statistical analysis. Recent naturalistic long-term outcome studies comparing ADM-treated and untreated individuals with diagnosed depression consistently corroborate the findings of Hughes and Cohen's review (Bockting, Hollon, Jarrett, Kuyken, & Dobson, 2015;Hengartner, Angst, & Roessler, 2018;Nuijen, ten Have, Tuithof, van Dorsselaer, & van Bon-Martens, 2014;Verduijn et al, 2017;Vittengl, 2017;Wang et al, 2017). Statistical adjustment for confounders (e.g.…”
Section: Psychological Medicinesupporting
confidence: 66%
“…In contrast, two major reviews of adult depression in general practice and the community (20 studies of almost 6000 participants, most with 3-7 years follow-ups) found that although 10-17% had a chronic course, up to 85% recovered for some time and that 35-60% experienced stable recovery (Steinert et al, 2014;van Weel-Baumgarten et al, 2000). Regarding outcome of non-treated community and general practice cases, multiple studies suggest that many depressive episodes (80-50%) are self-limiting as they remit within 3-12 months (Goldberg, Privett, Ustun, Simon, & Linden, 1998;Regier et al, 1998;Sareen et al, 2013;Spijker et al, 2002;Wang et al, 2017;Whiteford et al, 2013). For instance, Whiteford's (2013) metaanalysis of 19 studies of untreated depression in general practice settings estimated that 23% remit within 3 months, 32% within 6 months, and 53% within 12 months.…”
Section: Naturalistic Long-term Outcome Studiesmentioning
confidence: 99%
“…Although the expected differences in mental well-being between non-care-seekers and care-seekers, and insu cient care-perceivers and su cient care-perceivers, were observed at T1, we found no differences at T2. This result is in line with previous studies showing that the majority of those with common mental disorders who do not seek treatment remit (33,43,44). Results from a longitudinal study on men and women showed that among persons with untreated depression, anxiety or substance disorder, 50% remitted within three years (43).…”
Section: No Persistent Differences In Mental Well-being At T2supporting
confidence: 91%
“…They show that, similar to other high income countries, only 20% of those afflicted with a mental disorder in Germany utilize the health care system [ 5 , 6 ]. Up to 50% of untreated common mental disorders can remit spontaneously within a year [ 7 , 8 ]. This questions the call for early interventions, as it might be a good strategy for some individuals [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Up to 50% of untreated common mental disorders can remit spontaneously within a year [ 7 , 8 ]. This questions the call for early interventions, as it might be a good strategy for some individuals [ 7 ]. However, affected individuals often experience social damage, like worsening of the social climate among colleagues or with supervisors due to reduced work performance [ 9 ].…”
Section: Introductionmentioning
confidence: 99%